Analisis Pengendalian Internal atas Siklus Pendapatan Valuta Asing (Studi Kasus pada PT X) - Dewi, Gita Apsari; Wulandari, Anak Agung Ayu Intan (Politeknik Raflesia Press, 2024)
This study aims to analyze the internal control system applied to the foreign exchange revenue cycle by PT X. Weak internal control at PT X can lead to misappropriation by employees assigned to the sales, accounting, and/or cash functions. The study uses a qualitative case study approach. The researcher conducted interviews with internal staff related to the revenue cycle. Overall, the implementation of PT X's internal control can be said to be quite good, but still requires evaluation and improvement in aspects of risk monitoring, authorization of transaction evidence by related parties, and internal control over sales, accounting, and cash functions.